A Smartphone-Smartcard Platform for Implementing Contingency Management in Buprenorphine Maintenance Patients With Concurrent Stimulant Use Disorder - DeFulio, Anthony; Furgeson, Joshua; Brown, Hayley D.; Ryan, Shawn (Frontiers in Psychiatry, 2021)
Background and Objectives: Opioid agonist pharmacotherapies are effective in the treatment of opioid use disorder (OUD) but concurrent stimulant use is common and can lead to relapse and treatment drop out. Contingency management in combination with opioid agonist pharmacotherapy has broad beneficial effects in polysubstance users, including promoting drug abstinence and treatment retention, but clinic-based implementation can be burdensome. The present study was conducted to evaluate a contingency management intervention delivered via a smartphone-smartcard platform in OUD patients who had concurrent stimulant use disorder. Methods: Retrospective comparison of (n = 124) patients; half received the contingency management intervention and half were matched controls. Drug use and clinic attendance outcomes over four consecutive 30-day periods were analyzed with regression. Results: The intervention group showed consistently higher rates of drug abstinence and clinic attendance which were significant at the latter two timepoints. Discussion: Smartphone-smartcard platforms can facilitate dissemination of contingency management by surmounting or obviating key barriers to adoption. They appear to be convenient for all stakeholders, are easy to use, and facilitate high-fidelity implementation. Delivering contingency management via a smartphone-smartcard platform produces effects consistent with those observed when the intervention is delivered with substantially costlier and more burdensome in-person procedures.